Événement et trauma dans Doctor Atomic de John Adams - Mathieu Duplay (Transatlantica)
This article is based on the hypothesis that, by investigating the question of trauma, psychoanalysis has made an innovative contribution to the debate surrounding the concept of event, not so much because of the points explicitly made by Freud and his successors as because the ambiguities, contradictions, and aporias which characterize their discourse reveal some of the previously unseen difficulties inherent in such a discussion. Thus, the writer argues that a theory and/or poetics of event, however alien to the Freudian tradition, would benefit greatly by paying close attention to the lessons it teaches in this respect. John Adams’s 2005 opera Doctor Atomic, written in collaboration with Peter Sellars, is a case in point, not only because it deals with one of the most violent traumas in 20th‑century history—namely the nuclear test conducted at Los Alamos prior to the bombing of Hiroshima and Nagasaki—but also because, in addition to offering a potent meditation on the unthinkable, it reveals that all events, be they historical or aesthetic, call for new and as yet unformulated modes of thought ; as psychoanalysis suggests (sometimes in spite of itself), this is a clear sign of their traumatic nature.